RÓBERT KISS SZEMÁN: SLOVANSKÝ GOETHE V PEŠTI. JÁN KOLLÁR A NÁRODNÍ EMBLEMATISMUS STŘEDOEVROPSKÝCH SLOVANŮ (A Slavonic Goethe in Hungary. Ján Kollár and National Emblematism of Central European Slavs): Praha: Akropoli., 2014. 210 s. - Janiec-Nyitrai, Agnieszka (Slavia Centralis, 2020)
The article presents a monograph by Róbert Kiss Szemán entitled Slovanský Goethe in Pest, Ján Kollár a národní emblematismus středoevropských slovanů (A Slavonic Goethe inHungary. Ján Kollár and National Emblematism of Central European Slavs).
Keywords: Róbert Kiss Szemán; review; A Slavonic Goethe in Hungary; Slovak writers; Jan Kollar